Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4171/rsmup/126-12
|View full text |Cite
|
Sign up to set email alerts
|

Which Fields Have No Maximal Subrings?

Abstract: -Fields which have no maximal subrings are completely determined.We observe that the quotient fields of non-field domains have maximal subrings. It is shown that for each non-maximal prime ideal P in a commutative ring R, the ring R P has a maximal subring. It is also observed that if R is a commutative ring with jMax(R)j > 2 d0 or jR=J(R)j > 2 2 d 0 , then R has a maximal subring. It is proved that the well-known and interesting property of the field of the real numbers R (i.e., R has only one nonzero ring en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…In fact by the previous comment about the idealization, one can easily see that if K is any field with zero characteristic, then the ring + K is not submaximal, see [9,Example 3.19]. The existence of maximal subrings in commutative rings first studied in [3,4,[6][7][8][9]. In what follows, let us review some needed facts.…”
Section: Preliminaries On Maximal Subringsmentioning
confidence: 92%
See 4 more Smart Citations
“…In fact by the previous comment about the idealization, one can easily see that if K is any field with zero characteristic, then the ring + K is not submaximal, see [9,Example 3.19]. The existence of maximal subrings in commutative rings first studied in [3,4,[6][7][8][9]. In what follows, let us review some needed facts.…”
Section: Preliminaries On Maximal Subringsmentioning
confidence: 92%
“…In particular, it is shown that a ring T is submaximal if and only if T is finitely generated as a ring over a proper subring, see [3]. Fields and artinian (non)submaximal rings are completely determined in [6] and [7], respectively. In [8], it is proved that every noetherian ring R with R > 2 ℵ 0 and every infinite direct product of rings are submaximal.…”
Section: Preliminaries On Maximal Subringsmentioning
confidence: 99%
See 3 more Smart Citations